Instrumentos de Endomarketing na Melhoria de Processos de Software: um estudo sobre a indústria brasileira - Araújo, Diogo Pinheiro de (2014)
The software companies are increasingly qualifying and adapting the technical quality referrals as models and standards, due to strong competition and market demands. In software process improvement, organizations must pay attention to influential aspects such as the human factor, because it may be decisive in the success of these initiatives and which are not always taken into consideration. The objective of this study was to analyze the main Endomarketing actions presented and considered important in software process improvement, according to the perception of experts in the Brasilian context. The results show a possible way to treat the influence of the human fator in this area and show that the presence of Endomarketing actions is below what it should, compared to its importance, in the opinion of the respondents of this survey.